The Effect of Variations in the Side Skeg Angle on Drag and Seakeeping of a Barge - Hartono Yudo; Alfian Rizqy Mazy Barakah Barakah; Mohd. Ridwan; Zulfaidah Ariany (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2026)
This study aims to analyze the effect of variations in the side skeg angle on the total resistance and motion response of a barge. The research subjects consisted of a barge model without a skeg and a barge model with a triple-skeg configuration at side skeg angles of 140°, 150°, 160°, and 180°. Numerical simulations were conducted using Maxsurf Resistance software to obtain total resistance values and the Hydrodynamic Diffraction method to evaluate sway and yaw motion responses. Resistance tests were performed under two loading conditions full load and light load with a speed range of 2 to 6 knots. Seakeeping analysis was performed at a speed of 6 knots with regular waves 1 meter high and wave incidence angles of 0°, 45°, 90°, 135°, and 180°. The results of the study show that the addition of a skeg increases total resistance by a relatively small percentage, namely 1.68% - 1.74% under full-load conditions and 2.60% - 2.83% under light-load conditions. From a seakeeping perspective, the addition of a skeg tends to slightly increase the sway response but effectively reduces the yaw response, particularly at a transverse wave angle of 90°. Based on the balance between increased resistance and reduced yaw response, the 150° side skeg configuration can be considered the most balanced option for improving the barge’s directional stability without introducing significant additional resistance.